(untitled) - Chevance, René J. (Amsterdam,Boston, 2005)
The goal of this book is to present and compare various options one for systems architecture from two separate points of view. One, that of the information technology decision-maker who must choose a solution matching company business requirements, and secondly that of the systems architect who finds himself between the rock of changes in hardware and software technologies and the hard place of changing business needs.
Keywords: Computer architecture,System design,Client/server computing,Kiến trúc máy tính,Thiết kế hệ thống,Máy tính khách/Chủ